Magnetic and Thermal Characterization of Fe2.9wt.%Si for Magnetic Shielding Applications - Michele Quercio; Luca Santoro; Emir Poskovic; Raffaella Sesana; Aldo Canova (IEEE Access)
This article provides an in-depth analysis of the magnetic shielding and thermal properties of additively manufactured materials, focusing on the Fe2.9wt.%Si alloy produced via Laser Powder Bed Fusion (LPBF). The study compares these materials’ performance with conventional counterparts, particularly in the context of their application in magnetic shielding of a relay switch. The research integrates experimental findings from thermal imaging techniques to evaluate the efficiency of these materials under operational conditions, offering valuable insights into the future of additive manufacturing in high-performance magnetic shielding.